Design of Personal Data Security Scheme in Digital Public Service System Using AES-128 Cryptographic Algorithm - Fandi Fajar Maulana; Eka Jiparolim; Eko Nurcahyo; Jefry Sunupurwa Asri (Sean Institute, 2026)
Digital transformation in the public service sector has significantly accelerated the efficiency of government administration. However, this digitalization presents significant challenges related to cybersecurity, where the risk of personal data (Personally Identifiable Information) leakage poses a threat that could undermine public trust. This research aims to design a data security scheme in a public service system using the Advanced Encryption Standard (AES) cryptographic algorithm with a 128-bit key length. The research method used is conceptual design with a system development life cycle approach. The analysis results indicate that the AES-128 algorithm was selected due to its proven high performance and adequate level of security for public service needs. This design is recommended for implementation in public service databases to ensure the confidentiality of sensitive citizen data without overloading server performance.